Web Cross-site Inference Attack Detection and Avoidance using Defense Convolution Neural Network in Sensory Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The accelerometer and gyroscope motion sensor-based pass-web page detects attacks that may endanger the security of many mobile web clients, and measure the level of efficiency. Attack as a standard multi-stage problem also creates an imaginary framework that trains the phase within the training phase and predicts a new consumer input into the attack phase. To make the attack more robust and realistic, to design unique strategies and address quality data and conditions that require data classification and to conduct experiments to evaluate the impact of the use of invasive data protection techniques to reduce the accuracy of assumed attacks. The results show that researchers, smart phone companies, and app developers are paying close attention to cross-site-based motion sensor attacks, and begin designing and implementing powerful defense strategies.